Calcium bicarbonate as an antimicrobial, antiviral, and prion‑inhibiting agent (Review). Issue 1 (2022) - , TAKASHI ONODERA; SAKUDO, AKIKAZU; IWAMARU, YOSHIFUMI; YOKOYAMA, TAKASHI
No abstract available